RESEARCH AND OPTIMIZATION OF TEST DESIGN IN THE DEVELOPMENT OF BANKING SYSTEMS - Самофалова, Ганна; Калита, Надія (SWorldJournal, 2024)
The article discusses the creation of an optimal test plan for testing the electronic banking system. Banking systems are extremely complex in terms of architecture, requirements for information protection, integration with payment systems, which causes s